Teaching of industrial arts in the central elementary schools in the Division of Albay - De Jesus, Federico 1935- (s.n.], 1963)
This is an exploratory inquiry into the status of the teaching of industrial arts in the division of Albay. This study also determines the central elementary school's physical characteristics pertaining to industrial arts in the division of Albay, the characteristics of industrial arts teachers in relation to some factors, and the supervisory practices in the Division of Albay in the area of industrial arts.